2017
DOI: 10.3389/fpls.2017.01110
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Reveals Natural Variations Contributing to Drought Resistance in Crops

Abstract: Crops are often cultivated in regions where they will face environmental adversities; resulting in substantial yield loss which can ultimately lead to food and societal problems. Thus, significant efforts have been made to breed stress tolerant cultivars in an attempt to minimize these problems and to produce more stability with respect to crop yields across broad geographies. Since stress tolerance is a complex and multi-genic trait, advancements with classical breeding approaches have been challenging. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 166 publications
(209 reference statements)
0
49
0
Order By: Relevance
“…By utilizing evolutionary and historical recombination events at the population level, GWAS serve as an instrument to define complex trait differences at the sequence level (Lafarge et al, 2017). Likewise, GWAS can construe the evolution trend and/or the manmade selection of an essential trait (Wang and Qin, 2017). Methodologies for more advanced models have evolved from its simplest form called marker-by marker analysis (Lafarge et al, 2017).…”
Section: Mapping Of Genetic Loci (Qtl) and Genome-wide Association Stmentioning
confidence: 99%
See 3 more Smart Citations
“…By utilizing evolutionary and historical recombination events at the population level, GWAS serve as an instrument to define complex trait differences at the sequence level (Lafarge et al, 2017). Likewise, GWAS can construe the evolution trend and/or the manmade selection of an essential trait (Wang and Qin, 2017). Methodologies for more advanced models have evolved from its simplest form called marker-by marker analysis (Lafarge et al, 2017).…”
Section: Mapping Of Genetic Loci (Qtl) and Genome-wide Association Stmentioning
confidence: 99%
“…Moreover, a recent review on GWAS and QTL mapping concluded that natural variations responsible for drought resistance occur in crops and comprehensive approaches such as systems biological studies can be utilized to further elucidate the molecular mechanisms of identified loci (Wang and Qin, 2017). Combined analyses of GWAS and high-throughput phenotyping in rice showed meaningful insights into the genetic architecture of 15 essential traits related to morphology, biomass and yield (Yang et al, 2014b).…”
Section: Mapping Of Genetic Loci (Qtl) and Genome-wide Association Stmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we used linkage disequilibrium (LD)-based association mapping, a powerful tool for dissecting complex agronomic traits and identifying alleles that can contribute to crop improvement, in conjunction with candidate gene association analysis for detecting DNA polymorphisms (e.g. SNPs) or genetic markers within, or tightly linked to genes contributing to complex traits (Huang et al, 2011;Liu et al, 2017;Wang and Qin, 2017;Xiao et al, 2017). This approach has previously been successfully applied to detect allelic diversity of genes controlling crop drought tolerance, especially in rice and maize (Liu et al, 2013;Mao et al, 2015;Singh et al, 2015;Songyikhangsuthor et al, 2014;Wang et al, 2016;Xiang et al, 2017;Xiong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%